Beverage basics : understanding and appreciating wine, beer, and spirits - Small, Robert W. , 1947-; Couturier, Michelle , 1947-; Godfrey, Michael , 1959- (Wiley Publishing, 2011)
Offers information on the world's favorite alcoholic beverages, including their origins, modern production practices, and evaluating and enjoying each type of beverage